A DFT study of the mechanism and the regioselectivity of [3 + 2] cycloaddition reactions of nitrile oxides with α, β-acetylenic aldehyde. (1st November 2016) - Sobhi, Chafia; Nacereddine, Abdelmalek Khorief; Nasri, Lilia; Lechtar, Zohra; Djerourou, Abdelhafid
ABSTRACT: A DFT study of the (32CA) reaction of a series of some nitrile oxides with electron-deficient alkyne (3-phenylpropionlaldehyde) in gas phase and in toluene has been carried out using B3LYP functional with 6-31G(d) basis set. Two reactive channels 4- and 5-associated with the two regioisomeric modes have been located and characterised. These 32CA reactions are characterised by a low asynchronous one-step mechanism with a low-polar character. Analysis of the DFT reactivity indices indicates that the nucleophilic centre of the different nitrile oxides accounts for the 4-regioselectivity. Our calculations are in a good agreement with the experimental findings. Abstract :